Manajemen Kemiskinan Berbasis Komunitas: Pemberdayaan Lokal dalam Mengatasi Tantangan Ekonomi - Edy Suranta Karina Sembiring; Udin Bahrudin (Hikamatzu | Journal of Multidisciplinary, 2024)
This study examines community-based poverty management with a focus on local empowerment as a strategy to address economic challenges in communities. Through a participatory and collaborative approach, this study explores how local community empowerment can optimize local resources, increase economic capacity, and mitigate poverty. This study identifies best practices, challenges faced, and impacts of community-based programs in creating sustainable and locally relevant solutions. The results of the study are expected to provide new insights for policy makers, practitioners, and communities in designing and implementing poverty management strategies that are more effective and adaptive to changing economic dynamics